Regional policy of the Islamic Republic of Iran towards the energy of the Caspian Sea - Rafiee Saghalaksari Амир (Bulletin of the L.N. Gumilyov Eurasian National University. Political Science. Regional Studies. Oriental Studies. Turkology Series., 2022)
After the collapse of the Soviet Union and the establishment of independent republics, the Caspian Sea changed from an inland sea between Iran and the Soviet Union to an international sea with new neighbors. The use of the lake’s energy was of great importance to the littoral states, which sought to consolidate their independence and acquire foreign exchange resources in order to shape their financial resources for political security and independence. The transfer of these energy resources from the Caspian Sea to the consuming countries required the construction of new pipelines and transit routes, so that the newly independent countries could be removed from the control of the Russian government. Energy production and its transfer is an effective organizer to promote regional cooperation and economic link between countries, which in terms of national interests can be different achievements for each of the countries involved in transfer projects. In the meantime, an approach, and regional policies of the Islamic Republic of Iran to this issue can be important politically and in terms of security for the Islamic Republic of Iran. The main question is what effect can energy and its transmission through pipelines have on the national security of the Islamic Republic of Iran? The results of answering this question show that according to the position of the Islamic Republic of Iran in the interface between the energy resources of the Caspian Sea and the Persian Gulf, which is known as the world energy heartland and the confinement of the newly independent Caspian countries In addition to economic benefits, the participation of the Islamic Republic of Iran in transit and energy supply has made the international economy dependent on Iran, and this can lead to the political and economic security of the Islamic Republic of Iran.